Increasing Pregnant Women's Knowledge of Pregnancy Care through Community Based Health Education - Gustini Gustini; Asridawati Akib; Nordianiwati Nordianiwati (Edukasi Ilmiah Indonesia, 2025)
Pregnancy is a critical period that requires comprehensive knowledge and adequate health care to ensure maternal and fetal well-being. However, many pregnant women, especially in rural or underserved areas, often lack access to accurate information and resources related to pregnancy care. This community service program aims to increase pregnant women’s knowledge and awareness regarding essential aspects of prenatal care through community-based health education. The activity was conducted in collaboration with local health centers and involved 30 pregnant women from the X village area in the third trimester. The method used was interactive health education delivered through counseling sessions, visual aids, and discussion forums, facilitated by professional nurses specializing in maternal care. Pre and post-intervention questionnaires were used to measure knowledge improvement. The results showed a significant increase in participants' knowledge, particularly in Nutrition, danger signs during pregnancy, the importance of antenatal visits, and personal hygiene. Participants reported feeling more confident and prepared to manage their pregnancy after the intervention. This program demonstrates that structured, community-based education can effectively empower pregnant women to make informed decisions and adopt healthier behaviors, ultimately reducing maternal and neonatal risks